Mobile game design for understanding fractional conception in elementary school - D A Maharbid; T A Maharbid; Y Gumala; T Herman (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This research aims to design media for learning student’s conception on fraction headed for elementary level through mobile game. The indicators of conception related in this research were indicators definite on additions and subtraction. Research and development design research has already been pleased to collect data from third-grade elementary students in one of school in Cirebon Regency (25 participants: 8-10 years old). The instrument which is developed formed test with the expert judgement process. The result shows that every factual of conception have been developed and described. Design can be applied to make easier for students to comprehend conceptions. To summarize, the mobile game is able to define the 3th-grade elementary students’s conception on fractions.